New insights on transcriptional responses of genes involved in carbon central metabolism, respiration and fermentation to low ATP levels in Escherichia coli. (23rd August 2012) - Soria, Sandra; de Anda, Ramón; Flores, Noemí; Romero‐Garcia, Susana; Gosset, Guillermo; Bolívar, Francisco; Báez‐Viveros, José Luis
Abstract Adenosine‐5‐triphosphate (ATP) plays a fundamental role in many cellular processes such as transport, central carbon metabolism, biosynthetic reactions, macromolecular synthesis, signal transduction and cellular division. In addition, the intracellular [ATP]/[ADP] ratio in Escherichia coli plays an important role in controlling the specific rates of growth (µ), glucose consumption (qGlc) and oxygen uptake (qO2), as well as the transcriptome pattern in the cell, as was recently reported. In the current study, the energetic level (expressed as [ATP]/[ADP] ratio) was substantially reduced in E. coli strains by either over‐expressing the F1‐ATPase activity (JMAGD+) or inactivating ATP synthase (JMat−). The physiological characterization of the wild‐type JM101 strain and its derivative JMAGD+ and JMatp− strains was conducted in bioreactors containing minimal medium with glucose. The inactivation of the atp operon and F1‐ATPase overexpression significantly diminished the energetic level and cAMP concentration in derivative strains. Relative transcription levels of 105 genes involved in glucose transport, glycolysis, tricarboxylic acid (TCA) cycle, fermentation, respiration, transcriptional regulators, transcription and genes involved in stress were determined by using qPCR. Interestingly, in the JMAGD+ and JMatp− strains, having a reduced energetic level, many transcripts of glycolysis, TCA cycle and respiratory genes were down‐regulated when compared to wild type JM101. The transcriptional responses, detected in the strains with reduced energetic level show down‐regulation of genes involved in central carbon metabolism and respiration, these results are apposite to the observed trends of increased metabolic fluxes in glucose consumption, glycolysis, acetate synthesis, TCA cycle and respiration. Regulation mediated by CRP‐cAMP complex may explain some observed transcriptional responses of TCA cycle genes, since cAMP concentration and crp transcript level were significant reduced in the JMatp− mutant. Therefore, the substantial reduction of [ATP]/[ADP] ratio had a relevant effect on the CRP‐cAMP regulatory system (among other global regulators), which may trigger an extensive transcriptional response.